Physical Educators’ Stages of Development in Relation to their Teaching Concerns: A Review Study - Katsigianni Αφροδίτη; Derri Βασιλική (Inquiries in Physical Education and Sport, 2013)
The understanding of physical educators’ particular needs and factors that affect their work is considered a prerequisite for the design and the implementation of effective learning processes. Therefore, the educational and training programs taken place in pre- and in-service level should not be provided like common mass products but differentiated in accordance with teachers’ concerns in each stage of their professional development. Teaching concerns are defined as the teachers’ perceived worries and anxieties as a result of their interaction with the teaching environment. In case of physical educators, concerns are in close correlation with the particular nature of their subject matter. The present review examined the concerns developmental theory and the teaching concerns of the Physical Education teachers (pre- and in-service). A secondary purpose was the critical approach of the findings, in terms of the relation between concerns and teaching experience as well as other demographic characteristics such as gender or cultural and educational work environment. The results prove the important role of physical educators’ concerns to their professional development, both in pre- and in-service level.